Illegal, unreported and unregulated fishing in ASEAN - Lee, Wen Chiat; Viswanathan, K. Kuperan (2015)
Illegal, unreported and unregulated (IUU) fishing brings great losses to the economies.Understanding the reasons contributing to IUU fishing is crucial in reducing it.The factors are economic, institutional and social factors.This paper shows that economic factor is the main factor contributing to IUU fishing.This paper also highlights the two possible ways to curb the IUU fishing.One way is to reduce the revenue from IUU fishing and another way is to increase the cost of IUU fishing. There are three costs incurred in IUU fishing that can be reduced namely the operating, capital and risk costs.A framework of reducing the economic rent or profit of IUU fishing is developed and guidelines for reducing IUU fishing are also suggested.The guidelines are improved registration of fishing vessels, preventing entry of illegal fish products and most importantly, developing co-management of fisheries.All governments in ASEAN must work together with the stakeholders involved such as fishers, fishermen agencies or associations to exchange information to reduce transaction cost of IUU fishing.